The Social Intentionality of Battered Women's Agency in Ghana. (March 2018) - Adjei, Stephen Baffour
There is a growing body of research which suggests that victims of intimate partner violence (IPV; mostly women) continue to remain in abusive relationships. Many of the Western psychological theorisations focus on battered women's personal dispositions and/or the self-creating (individualistic) view of agency to explain why victims remain in violent relationships. These studies seem to suggest that staying in a violent relationship is a personal decision that victims make in free will, and that victims who continue to stay fail to act on their own behalf. Drawing upon the Ghanaian communal conceptualisation of personhood and the social norms of marriage and divorce, this study questions the individualistic theorisations of battered women's decisions to stay in or leave abusive relationships. The article argues that battered women's agency in negotiating the stay/leave decisions in abusive relationships does not only originate in an independent autonomous self, nor constituted by a person's internal motives, but also, and even primarily, it is culturally grounded and dependent on social relations for its realisation. The article concludes that the agency of abused women in Ghana has a social intentionality, in the sense that battered women's intentional behaviour in marital relationships is both constituted by self and constrained by their relational embeddedness.